Structural characterization and optical constants of p-toluene sulfonic acid doped polyaniline and its composites of chitosan and reduced graphene-oxide - Usman, Fahad; Dennis, John Ojur; Ahmed, Abdelaziz Yousif; Seong, Khe Cheng; Fen, Yap Wing; Sadrolhosseini, Amir Reza; Meriaudeau, Fabrice; Kumar, Pradeep; Ayodele, Olumide Bolarinwa (Elsevier, 2020)
Para-Toluene sulfonic acid doped polyaniline (PANI), PANI/chitosan composites, PANI/reduced graphene-oxide composites and a ternary composite comprising of PANI, chitosan and reduced graphene-oxide have synthesised via oxidative polymerisation of aniline by Ammonium peroxydisulfate (APS). FTIR, XRD, FESEM and UV-VIS techniques were performed for the confirmation of the successful synthesis. The fundamental optical parameters such as, complex refractive index, complex dielectric constants and optical conductivity of the PANI and the composites were investigated in the UV-VIS-NIR range. The results show a clear dependence on the constituent component such as sulphur as well as the absorbance values of the polymers. This study would therefore serve as initial solution to the scarcity of studies on the optical contants of p-toluene sulfonic acid doped polyaniline and its composites that could have many potential electrical, optical and optoelectronic applications.